Effects of an abbreviated obesity intervention supported by mobile technology: The ENGAGED randomized clinical trial. Issue 7 (11th May 2017) - Spring, Bonnie; Pellegrini, Christine A.; Pfammatter, Angela; Duncan, Jennifer M.; Pictor, Alex; McFadden, H. Gene; Siddique, Juned; Hedeker, Donald
Abstract : Objective: To determine the effects on weight loss of three abbreviated behavioral weight loss interventions with and without coaching and mobile technology. Methods: A randomized controlled efficacy study of three 6‐month weight loss treatments was conducted in 96 adults with obesity: 1) self‐guided (SELF), 2) standard (STND), or 3) technology‐supported (TECH). STND and TECH received eight in‐person group treatment sessions. SELF and STND used paper diaries to self‐monitor diet, activity, and weight; TECH used a smartphone application with social networking features and wireless accelerometer. Results: Weight loss was greater for TECH and STND than SELF at 6 months (−5.7 kg [95% confidence interval: −7.2 to −4.1] vs. −2.7 kg [95% confidence interval: −5.1 to −0.3], P < 0.05) but not 12 months. TECH and STND did not differ except that more STND (59%) than TECH (34%) achieved ≥ 5% weight loss at 6 months ( P < 0.05 ) . Self‐monitoring adherence was greater in TECH than STND ( P < 0.001), greater in both interventions than SELF ( P < 0.001), and covaried with weight loss ( r (84) = 0.36‐0.51, P < 0.001). Conclusions: Abbreviated behavioral counseling can produce clinically meaningful weight loss regardless of whether self‐monitoring is performed on paper or smartphone, but long‐term superiority over standard of care self‐guided treatment is challenging to maintain.